The impact of type 2 diabetes on adolescent and family functioning and healthcare use: findings from the National Survey of Children’s Health - Noël C. Slesinger Roy; Megan O. Bensignor; Wendy S. Grolnick; Peter B. Scal (Frontiers in Endocrinology)
IntroductionType 2 diabetes is a complex chronic illness requiring significant support. The goal of this study is to better understand stressors associated with type 2 diabetes for adolescents and caregivers and their impact on family functioning and health status.MethodsUsing the National Survey of Children’s Health, this study examined differences in adolescent mental health, family and caregiver functioning, and medical service usage in pediatric type 2 diabetes, asthma, special healthcare needs, and adolescents without chronic illness.ResultsAdolescents and families with type 2 diabetes demonstrated higher mental health concerns, poorer parental coping and family resilience, and higher use of emergency care than one or more of the comparison groups. Emergency care needs were also higher than expected for type 2 diabetes.DiscussionAdolescents with type 2 diabetes and their caregivers reported significant stressors and functioning concerns as compared to adolescents with and without another chronic illness. These families also required more intensive care needs, highlighting the need to support adolescent and family psychosocial functioning in the context of type 2 diabetes.